Pengaruh Perkembangan Pengeluaran Pemerintah dan Penganggaran terhadap Masyarakat Penerima Bantuan Sosial yang Terdampak Banjir - Yescenia Sigiro; Yulce Ketrina Karubuy; Eki Monalisa Br Surbakti; Suriyani Br Ginting; Yohanna Sitanggang (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze the impact of government expenditure development and government budgeting on the social assistance recipients affected by floods. The research approach uses a quantitative method with a total of 50 respondents selected through sampling techniques. Data processing was conducted using SPSS software with various statistical tests, including validity test, reliability test, multiple linear regression, t-test, and F-test. The results show that the development of government expenditure has a significant impact on the condition of the social assistance recipients. Additionally, government budgeting also has a significant impact on the effectiveness of social assistance distribution after the disaster. Simultaneously, both variables have a strong influence on the social assistance recipients, as reflected by the significant F-test value and the coefficient of determination (R Square) of 0.518. This means that 51.8% of the variation in the condition of social assistance recipients can be explained by the development of government expenditure and government budgeting. These findings highlight the importance of appropriate expenditure and budgeting policies to enhance the effectiveness of social assistance distribution, especially in disaster situations.